A DISCOURSE ANALYSIS OF CLAUSES OF ENGLISH USE ON THE BABY'S PRODUCTS - SRINASTITI, NORANI (2009)
The information of the products is very important for community in order to choose the best and the comfortable products that are used by people or babies. This research paper studies the thematic structure pattern of clauses of English use on the baby's products. The objective of this research is to examine the theme-rheme patterns of clauses of English use on the baby's products. The data are taken from the English use on the package of the baby's products. The method of the data collection is observation and documentation. The writer takes 40 data of 10 baby's products in different brand. The writer uses descriptive qualitative method. By using this method, the writer describes the data based on thematic structure pattern or Theme-Rheme in clauses. The result of the research shows that the theme-rheme pattern of clause is represented in (1) The Transitivity Structure pattern which has six elements, they are: Process, Agent, Affected, Recipient, Attribute, and Circumstance; (2) The Mood Structure pattern which has two elements, they are: Mood and Residue; (3) and The Thematic Structure pattern which has two elements, they are: Theme and Rheme. In the Thematic Structure, she finds the types of Theme they are: (a) Ideational theme, it can separate into two, they are: Unmarked topical theme (divided into three, they are: Nominal group as theme, Nominal group Complex as theme, and Embedded clause) and Marked topical theme (divided into three, they are: Adverbial as theme, Prepositional Phrase as theme, and Complement as theme), (b) Textual theme and (c) Interpersonal theme. The research finding of the data, they are: Ideational theme (adverbial as theme): 15%, Ideational theme (prepositional as theme): 7.5%, Ideational theme (complement as theme): 25%, Ideational theme (nominal group as theme): 12.5%, Textual theme there are: 7.5%, Interpersonal theme: 7.5% and the last is Theme in Imperative: 25%. The results of rheme are the new information or the rest of the clauses of all the data and it comes at the end of all the clauses.